2019
DOI: 10.5194/adgeo-47-1-2019
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the Gondwana breakup at the Southern South America by apatite fission-track analyses

Abstract: Apatite fission-track (AFT) analyses, applied to Southern Brazil and Uruguay samples, was employed aiming to understand the low temperature history of the Dom Feliciano Belt Segment. The Dom Feliciano Belt formed during the Neoproterozoic to Early Paleozoic, linked to the Brasiliano/Pan-African Orogeny. Twenty-four samples were dated, and confined track lengths of twenty samples were measured. The spatial distribution of ages shows three domains with different evolution cut by shear zones and, or suture zones … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 62 publications
0
10
0
2
Order By: Relevance
“…A plot of the MTLs against AFT central ages (Fig. 4), including published data (Kollenz 2015;Gomes & Almeida 2019), does not show a clear pe (Green 1986), which is characteristic of reheating with partial reset of AFT ages in a region.…”
Section: Apatite Fission-tracksmentioning
confidence: 76%
See 3 more Smart Citations
“…A plot of the MTLs against AFT central ages (Fig. 4), including published data (Kollenz 2015;Gomes & Almeida 2019), does not show a clear pe (Green 1986), which is characteristic of reheating with partial reset of AFT ages in a region.…”
Section: Apatite Fission-tracksmentioning
confidence: 76%
“…1), where a very complex thermal history has been reported (Jelinek et al 2003;Karl et al 2013;Hueck et al 2018a). Further south of this region, thermochronometry studies have reported mainly pre-rift Paleozoic cooling phases in southernmost Brazil (Borba et al 2002(Borba et al , 2003Oliveira et al 2016;Machado et al 2019), Uruguay (Kollenz 2015;Hueck et al 2017;Gomes & Almeida 2019) and Argentina (Kollenz et al 2017). These were generally linked to Paleozoic orogenic cycles on the active SW margin of Gondwana and the geodynamics of Gondwana breakup.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…participation in EU elections), are significantly correlated with demographic dynamics and built infrastructure characteristics. Melillos et al (2018) aim at exploring the importance of monitoring military landscapes in Cyprus using Earth Observation. The rising availability of remote sensing data provides adequate opportunities for monitoring military landscapes and detecting underground military man-made structures.…”
mentioning
confidence: 99%